Moore And Chien Correlation To Address The Issue Of Hole Cleaning In Guba Field – Libya (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Hole cleaning and hydraulics are important part of drilling operations that need to be carefully reviewed and incorporated in drilling program. Poor hole cleaning could lead to various problems like slow rate of penetration (ROP), excessive torque and drag, excessive wear on bit, pipe sticking problems, and possibly fracturing of formation.In this work, Since hole cleaning is a major problem associated with drilling operations. There is an evaluation of the effect of the drilling fluid rheology parameters and flow rate on hole cleaning. Correlation methods such as Moore and Chien correlation have been made to provide the most suitable approach to address the issue of a hole cleaning. On the other hand, also explains the effect of the flow rate in the equivalent circulating density (ECD) in terms of frictional pressure loss in the annulus. The result of analysis demonstrates how the rheology parameters and flow do affect the hole cleaning and concludes that the ECD and frictional pressure loss in the annulus are affected by the flow rate.